2018
DOI: 10.1038/s41598-018-35319-1
|View full text |Cite
|
Sign up to set email alerts
|

Employing a spatio-temporal contingency table for the analysis of cork oak cover change in the Sa Serra region of Sardinia

Abstract: Land cover change analyses are common and, especially in the absence of explanatory variables, they are mainly carried out by employing qualitative methods such as transition matrices or raster operations. These methods do not provide any estimation of the statistical significance of the changes, or the uncertainty of the model and data, and are usually limited in supporting explicit biological/ecological interpretation of the processes determining the changes. Here we show how the original nearest-neighbour c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…Cork oak (Quercus suber L.) forest cultivation is an important economic activity in many Mediterranean countries; it is cultivated on about two million hectares-61% in Spain and Portugal, 33% in Morocco, Algeria and Tunisia and 6% in Italy and France [1]. Cork oak usage is correlated to the preservation of biodiversity and the reduction of CO 2 emissions.…”
Section: Musty and Moldy Taintmentioning
confidence: 99%
See 1 more Smart Citation
“…Cork oak (Quercus suber L.) forest cultivation is an important economic activity in many Mediterranean countries; it is cultivated on about two million hectares-61% in Spain and Portugal, 33% in Morocco, Algeria and Tunisia and 6% in Italy and France [1]. Cork oak usage is correlated to the preservation of biodiversity and the reduction of CO 2 emissions.…”
Section: Musty and Moldy Taintmentioning
confidence: 99%
“…Cork oak usage is correlated to the preservation of biodiversity and the reduction of CO 2 emissions. The harvest of the cork bark does not necessitate tree cutting because the rhytidome has high insulation capacity; as such, this species produces suckers to recover quickly after a fire and to resist cold and wind [1]. Cork oak forest cultivation contributes to the protection of the soil, the creation of the landscape and the regulation of hydrological cycle [2].…”
Section: Musty and Moldy Taintmentioning
confidence: 99%
“…There is increasing evidence of a declining trend in cork oak populations, especially at the edge of the species' natural distribution range (Vessella et al 2017, Matías et al 2019. Many factors have been invoked to explain the ongoing process, which is bound to increase in the forthcoming decades based on current climate change scenarios (Matías et al 2019), and due to other growing threats, such as overgrazing, soil pathogens and land-use changes (Dettori et al 2018). In the Mediterranean region, climatic forecasting seem to indicate a rise in temperatures and a reduction in precipitation, which will probably decrease the potentially suitable areas for cork oak, especially in the southern edge and at lower altitudes; accordingly, northward and upward shifts could occur (Vessella et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As other Mediterranean forest systems, a number of previous studies have reported that cork oak ecosystems are in decline or endangered. The spatial distribution and vitality of Quercus suber L. woodlands are affected by several complex and sometimes interrelated disturbance factors (Luciano and Roversi 2001;Filigheddu 2003, 2016;Silva and Catry 2006;EEA 2007;Pereira 2007;Acácio et al 2009;Bugalho et al 2011;FAO 2013;Oubrahim et al 2015;Acha and Newing 2015;Oliveira et al 2016;Dettori et al 2018). Wildland fires represent one of the most relevant disturbances for cork oaks, as well as for other forests in the Mediterranean Basin.…”
Section: Introductionmentioning
confidence: 99%